1984
DOI: 10.1067/mva.1984.avs0010877
|View full text |Cite
|
Sign up to set email alerts
|

Patency in canine inferior vena cava grafting: Effects of graft material, size, and endothelial seeding

Abstract: We studied 117 inferior vena cava (IVC) replacements in dogs to determine the effects of graft material, graft size, endothelial seeding, and cultured endothelial linings on graft patency. As a control, the IVC was removed and reimplanted in 11 dogs. Dacron (n = 7) and expanded polytetrafluoroethylene (e-PTFE) grafts (n = 12) were seeded immediately with the use of enzymatically derived autogenous jugular vein endothelium. Cultured linings were prepared for e-PTFE grafts (n = 9) by inoculating the graft with j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The appropriate porosity, allowing for cell migration and supporting natural ECM (extracellular matrix) secretion, is important to graft patency as is a healthy endothelial layer. A canine study, which examined the effects of biomaterial and endothelial cell seeding revealed that simply applying endothelial lining in dacron and e-PTFE (expanded-Polytetrafluoroethylene) grafts was not a deciding factor for patency, but, the biomaterial used to construct the vessel played a significant role [6]. The study results concluded that isodiametric naturally harvested scaffolds performed best to maintain patency [6].…”
Section: Biomaterials For Vascular Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate porosity, allowing for cell migration and supporting natural ECM (extracellular matrix) secretion, is important to graft patency as is a healthy endothelial layer. A canine study, which examined the effects of biomaterial and endothelial cell seeding revealed that simply applying endothelial lining in dacron and e-PTFE (expanded-Polytetrafluoroethylene) grafts was not a deciding factor for patency, but, the biomaterial used to construct the vessel played a significant role [6]. The study results concluded that isodiametric naturally harvested scaffolds performed best to maintain patency [6].…”
Section: Biomaterials For Vascular Tissue Engineeringmentioning
confidence: 99%
“…A canine study, which examined the effects of biomaterial and endothelial cell seeding revealed that simply applying endothelial lining in dacron and e-PTFE (expanded-Polytetrafluoroethylene) grafts was not a deciding factor for patency, but, the biomaterial used to construct the vessel played a significant role [6]. The study results concluded that isodiametric naturally harvested scaffolds performed best to maintain patency [6]. Graft porosity allows for cell adherence as well as migration and diffusion of important healing factors critical to the remodeling responses [7–9].…”
Section: Biomaterials For Vascular Tissue Engineeringmentioning
confidence: 99%
“…Of these, one reported clinical patency at 5 months [19], one clinical and radiological patency at 8 months [20] and one an occlusion [21]. One animal study [22] involving 117 dogs compared the patency of Dacron with PTFE. All of the Dacron grafts occluded by 30 days, but the patency of the PTFE grafts was surprisingly low, at 28%.…”
Section: Commentmentioning
confidence: 99%
“…Both in vitro [23] and in vivo [24] studies comparing the thrombogenicity of Dacron with PTFE have shown that Dacron leads to the deposition of more fibrin and platelets. In animal studies with Dacron over the last 18 years, some have tried seeding the graft with endothelial cells to enhance patency in the venous system, with some statistically significant success recently, but no clinical trials as yet [22,25–27].…”
Section: Commentmentioning
confidence: 99%
“…1°13 Another problem is low retention of seeded ECs on grafts; as few as 17% of seeded ECs reportedly remain adherent to implanted vascular prostheses 24 hours after implantation when the preclotting method of seeding is used} 4,~s Perhaps because of some or all of these problems, one study of EC seeding of polytetrafluoroethylene (PTFE) inferior vena cava (IVC) prostheses in dogs found no reduction of thrombus-free surface area after seeding. 16 In another study low-density seeding (with 2.5 to 4.5 × 104 EC/cm 2 of PTFE graft sur-face) was used on PTFE, and thrombus-ftee area was significantly improved when compared to unseeded PTFE conduits, yet complete EC coverage and freedom from grossly visible thrombus formation was not seen even 4 weeks after surgery, i7…”
mentioning
confidence: 99%